Effects of close-to-nature forest management on carbon stocks in Pinus tabulaeformis plantations in northern China - Jinmei Xu; Huiling Tian; Jun Xiao; Zhaochen Li; Wenfa Xiao; Runsheng Yin (Frontiers in Forests and Global Change)
Scientifically understanding how to increase the carbon stocks of plantations under the great demand for forest carbon sinks to meet the 2.0 or 1.5°C target of the Paris Agreement is attracting mounting attention. As one of the most promising plantation management regimes, it is pertinent to ask whether close-to-nature management could improve the carbon stocks of Pinus tabuliformis plantations in trees, shrubs, grasses, litter, and soil. This study investigated and analyzed the effects of close-to-nature management, in comparison with no human intervention, on the carbon stocks of P. tabuliformis plantations in three age-classes (10-, 47-, and 56-year-old stands) over 6 years in the Wangyedian Experimental Forest Farm of Chifeng, China. The results showed under close-to-nature management and no human intervention, the amounts of carbon stocks of P. tabulaeformis plantations were similarly ranked (soil > trees > litter > grasses > shrubs), and the trees, vegetation, and ecosystem carbon stocks of P. tabuliformis plantations increased significantly with stand age (p < 0.05). Close-to-nature management increased the annual increment of the tree carbon stock in 47- and 56-year-old stands, as well as that of the soil carbon stock and ecosystem carbon stock in 56-year-old stands, and also that of litter carbon stock in all stands, whereas it decreased both soil and ecosystem carbon stocks’ annual increment in 10- and 47-year-old stands. The annual increment of the ecosystem carbon stock was greater in 56-year-old (7.49 Mg∙hm−2∙a−1) than 47-year-old stands (5.82 Mg∙hm−2∙a−1) under close-to-nature management, but vice versa under no human intervention (56-year-old: 3.98 Mg∙hm−2∙a−1 vs. 47-year-old: 6.78 Mg∙hm−2∙a−1). This inverted response indicates that reasonable management measures could increase the ecosystem carbon stock of mature forest as defined by current Chinese age classification standards. Additionally, since the tree carbon stock of ca. 60-year-old P. tabuliformis stands is still growing, this suggests the plantation maturity of this pine specie can and should be extended to produce timber with larger diameters that sequester more carbon.